Pemeriksaan dan Pendidikan kesehatan di Lingkungan Pimpinan Cabang Muhammadiyah Mulyorejo Surabaya - Firdausi Nuzula; Sayful Rochman; Muhibbul Ariq; Quratul Mawaddah; Dita Rahmawati (Rena Cipta Mandiri, 2025)
Health is a fundamental aspect of human life that determines the quality of life and productivity of society. The level of public knowledge about health is often a key factor in efforts to prevent and control disease. Health education is a strategic effort to increase public understanding and awareness of the importance of maintaining health, including implementing healthy lifestyles and early detection of various diseases (WHO, 2018). The aim of this service activity is in the form of health checks and counseling around the Mulyorejo Muhammadiyah Branch Leadership (PCM) area to find out about public health and increase public knowledge to avoid non-communicable diseases (PTM). The method used in this activity is to carry out health checks, namely checking blood sugar, cholesterol and also uric acid and counseling each individual after the examination. This educational activity, which is carried out in conjunction with health checks, provides important insight for the community about their current health condition and the preventative steps that need to be taken. It is hoped that the results of this activity can become the basis for developing more comprehensive and sustainable health programs in the future.